The Knowledge and Attitude to Species Invasion Issue in Greenway Planning: A Study in China - Fan Fu; Zhao Caijun; Lin Guangsi (Fábos Conference on Landscape and Greenway Planning, 2013)
Greenway is important green infrastructure which has ecological, recreational and cultural/historic functions applied in macro(country), medium(region) and micro(city) levels. Generally, greenway is in linear or reticular forms so that it is called “way”. Greenway has a long history in United States and Europe, and many successful projects have been implemented. Conversely, greenway has a very short history in China, because China lately started it urbanization in 1990s with a low degree of urbanization, which had grown from 26.37% in 1991 to 36.22% to 2000. Thus, for a long time, Chinese landscape architects had focuses on the level of urban area and lower ones, rather than higher levels of region and nation. The first paper on greenway in China published on a journal of urban planning, introducing greenway movement in United States [1]. Unfortunately, this paper had not drawn enough attention of landscape architects, because of the disciplinary separation of landscape architecture and urban planning in China. There had been no paper on greenway for 10 years since then. In the new century, greenway starts to be paid attention. In 2001, it was first time when paper on greenway was published in a journal of landscape architecture in China, which introduced the development of greenway in United States [2]. After it, the number of papers on greenway increases. Two groups of papers selected from the 2rd Fobos International Conference on Greenway and Landscape Planning 2010 were published as special topic on the Journal of Chinese Landscape Architecture and the Journal of Landscape Architecture, China, which introduced greenway development and projects in United States and European countries to Chinese professionals, and evoked wide repercussions. Two books on greenway, Greenways: A Guide To Planning Design And Development by Charles Flink (Author), Robert Searns (Author), Loring LaB. Schwarz (Editor) and Ecological Networks And Greenways: Concept, Design, Implementation by Rob H. G. Jongman and Gloria Pungetti (Editor) was published in China in 2009 and 2011, and became “must read” books for greenway planners. As the result of rapid urbanization, a growth from 36% to 50% during the first decade of new century, and rethinking of urban-rural integration, greenway projects starts in China. Though Zhejiang government first made its provincial greenway planning in 2004, Guangdong is the first province who started greenway implementation in 2010. Guangdong plans to build 8770 km province-level greenway by 2015, and it had finished 2372 km province-level greenway and 4978 km city-level greenway by the end of 2012. Stimulated by Guangdong, other provinces or metropolises have started their ambitious plans of greenways, as rapid and colossal as their urbanization plans (Table 1). Moreover, during the project of Supplying Water from South China to North, and the project of historic preservation of the Grant Canal for World Heritage application, national greenways are surmised to be built along the canals and pipelines. Now, greenway planning projects have been a new growth point of landscape architecture industry. Though many landscape architecture firms and contractors benefit from the prosperity of greenway, as well as the users, the speed of greenway movement is worrying. The procedure of decision making is hasty. Many decision makers don’t know what the definition of greenway is, how it functions, whether they need it, but they decide to build it because other provinces or cities have greenway plans. Some even believe greenway is just another name for trial or parkway. The hasty decision also causes irrational plans characterized by oversized scale, fast period, and repeated duplication, which leave insufficient time to study, plan, and implement. Moreover, the greenway planners don’t have enough experience and knowledge so that they underestimate the potential hazards. Therefore, under such a situation, fast and large greenway plans might lead to grave consequences.
Keywords: greenways; invasive species; china; case study; asia